The influence of lean-oriented team performance management practices on lean service requirements - Ulrych, Wojciech (Contemporary organisation and management. Challenges and trends, 2020)
The aim of this paper is to show the influence of lean-oriented team performance management (TPM) practices on lean service (LS) requirements within Polish service departments. To do this, it was necessary to identify how lean-oriented teamwork practices reflect the practices and stages of the universal TPM of selected authors. Exploratory factor analysis (EFA) by generalized least squares (GLS), Kaiser’s normal varimax rotation methods and secondary data were used. The results reveal that lean-oriented TPM practices resemble universal TPM, and also that they help in the implementation of LS requirements, and the team has its share in managing individual performance.